Por el curso de las quebradas hacia el ‘territorio integral indígena’: autonomía, frontera y alianza entre los awajún y wampis - Garra, Simone (2014)
In the framework of the self-determination process of ‘indigenous integral territories’ led by the Coordinadora Regional de los Pueblos Indígenas (CORPI), the Awajún and Wampis organizations have been defining their territories in a series of intra- and inter-ethnic meetings, objectifying their relationship with their respective geographic areas. In this sense, such process of indigenous autonomization interacts with State models and political institutions. In this paper,on the basis of our participation in anthropological reports to support the demand for recognition of ‘integral territories’, we try todescribe and analyze the dynamics of local autonomy, supra-local alliances and inter-ethnic borders among the Awajún and Wampis and how such dynamics have mobilized them facing the increasing pressure by the national society and global capitalism.